Top 10 Health Issues Faced by Maine People - Mills, Dora (Maine Policy Review, 2003)
In this article Maine’s Bureau of Health Director, Dr. Dora Anne Mills, outlines the top 10 health issues facing Mainers today. As Mills points out, many chronic health issues would be greatly alleviated if people ate less and better, exercised more, and didn’t smoke. Despite the role of self determination in affecting these behaviors, Mills argues that all can be influenced through more proactive policies at the local, state, and national levels, and changes to our surrounding environments. Only when neighborhoods, schools, workplaces, and communities are structured in ways that promote healthy lifestyles will there be real changes in the health trends of our time.
Keywords: Maine; health; public health